Dynamic Simulation Of Continuous Polystyrene Reactor Using Python - Kumaresan, Vengdasan (Universiti Sains Malaysia, 2022)
The COVID-19 epidemic has caused global upheaval in a number of ways and from a variety of viewpoints. One of the fields where this scenario has had a considerable influence is education. This is due to the fact that students can no longer meet with professors and lecturers in person. Chemical Engineering laboratory practise is no longer done face-to-face and manually. To address this issue, an alternative approach that allows students to study and conduct their own laboratory sessions is necessary. As a result, computer simulation is regarded as the best solution to this problem. This mathematical modelled user interphase simulation has certain advantages since it allows students to analyse high-cost equipment such as polymer reactors. Students are not exposed to high-cost technology in typical laboratories due to funding restrictions. They were able to obtain a better knowledge of the relevant processes and properties by using simulation. The primary process in this work is the simulation of a polystyrene polymerisation reactor, and the reactor monomer conversion is employed as the main evaluation metric. This thesis presents the building and simulation of a solution polymerisation reactor simulator for polystyrene in a continuous stirred tank, CSTR, using Python 3.10. The numerical solution to the ordinary differential equations, which was extracted from the literature, was solved by creating a module that was utilised in conjunction with the NumPy, Scipy, and Matplotlib modules included in the Spyder, which is an integrated development environment (IDE) for Python. Python was used to provide a realistic solution that takes into account the impact of the non-linear polymerisation kinetics stated in the literature. The findings revealed that at the stated conditions, a maximum monomer conversion of approximately 73.97 percent could be accomplished at a maximum operating time of about 400 hours to yield a poly-dispersion polymer with an index of 1.51, which is validated with literature values with acceptable error percentages, which is below 30%. It is also proved that Python, like any other programming language, can be used to conduct comparable experiments with equal success. The initiator, monomer, and cooling jacket fluid flowrates were set as manipulated variables in that simulator. In this thesis also, the effect of this manipulated variable on the polystyrene reactor is also discussed using the continuous polystyrene polymerisation reactor simulator, which was created using Python. It was observed that the monomer conversion of the polystyrene polymerisation increased with the manipulated variables, which are volumetric flowrate of initiator, monomer, and cooling jacket fluid. It has also been observed that the monomer conversion of polymerization has its highest value at 150 L/h initiator flowrate, 278 L/h monomer flowrate, and 571.6 L/h cooling jacket fluid flowrates. The effects of the initiator, monomer, and cooling jacket fluid flowrates on other variables, such as monomer and initiator concentration, reactor and jacket temperature, viscosity, weight and number average molecular weight, and polydispersity, were also studied in this thesis.